A Study on Dynamic Relationship Between Oil, Gold, Forex and Stock Markets in Indian Context. Issue 1 (June 2016) - Ingalhalli, Varsha; G., Poornima B.; Reddy, Y. V.
Indian economy in the recent past had experienced a volatile situation in its financial markets. Forex markets witnessed continuous weakening of rupee against dollar, followed by rise in crude oil prices, gold prices, inflation rate which made RBI to interfere with its hike in policy rates to curb the inflation. Effect of one market on another market is not a new thing, but the variations in the degree of impact and co-movements between the markets need to be examined. The main objective of this article is to study the causal relationship between oil, gold, forex and stock markets, for a period ranging from January 2005 till July 2015. This study employs the Granger causality test. The results indicate that the existence of only unidirectional relationship among the variables. The Granger causality test reveals that oil prices contribute towards development and forecasting of exchange rate and gold prices, whereas fluctuations in oil prices are granger caused by Sensex.